Предмет: Алгебра,
автор: noskova2012
Помогите с решением пожалуйстаа
Приложения:
Ответы
Автор ответа:
0
1) a)sqrt 5(sqrt 10 + sqrt 5 - sqrt 40 / 2) = sqrt 5(sqrt 10 + sqrt 5 - sqrt 10)=sqrt 5 * sqrt 5 = 5
b) 5 - 2sqrt 10 + 2 = 7 - 2 sqrt 10
2)a) (6-sqrt a)(6+sqrt a) / (6-sqrt a)=6+ sqrt a
b)sqrt 5(sqrt 5-1)/sqrt 3(sqrt 5 -1)=sqrt5 / sqrt 3
3)a)3sqrt5 b)5sqrt13 - 5sqrt 3 / 10 = sqrt 13- sqrt 3 / 2
b) 5 - 2sqrt 10 + 2 = 7 - 2 sqrt 10
2)a) (6-sqrt a)(6+sqrt a) / (6-sqrt a)=6+ sqrt a
b)sqrt 5(sqrt 5-1)/sqrt 3(sqrt 5 -1)=sqrt5 / sqrt 3
3)a)3sqrt5 b)5sqrt13 - 5sqrt 3 / 10 = sqrt 13- sqrt 3 / 2
Автор ответа:
0
Спасибо большое
Автор ответа:
0
1)a)5 б)7–2-/10
2)a)6+-/а б)-/15:3
3)а)3-/5 Б) -/13+-/3:2
4)~~~~~
5)а)-3.2 Б)у2 в)х3
6)а)-/12 б)-/а2*2 в)-/–3х
2)a)6+-/а б)-/15:3
3)а)3-/5 Б) -/13+-/3:2
4)~~~~~
5)а)-3.2 Б)у2 в)х3
6)а)-/12 б)-/а2*2 в)-/–3х
Похожие вопросы
Предмет: Русский язык,
автор: aselya11156
Предмет: Қазақ тiлi,
автор: tojsybekovavenera
Предмет: Литература,
автор: sofia123357
Предмет: Физика,
автор: skatyshka
Предмет: Алгебра,
автор: shklivechannel